Integration of Innovative Learning Methods in 21st Century Skills Development: A Systematic Review - Fitriyani, Riska; Nurlela, Nurlela; Aqil, Nur; Marba'i, Marba'i; Amelliyah, Rizqi; Khairani, Deby Rahma; Musliman, Acep; Rifai, Dede Syukrillah (Paedagogie, 2026)
The rapid advancement of technology and the evolving demands of the global workforce have underscored the importance of integrating 21st-century skills into education. Science, Mathematics, and Technology Education (MIPA) plays a pivotal role in developing the technical, cognitive, and interpersonal skills essential for students to thrive in a knowledge-driven economy. This systematic review aims to explore the integration of innovative learning methods to foster critical 21st-century competencies, such as digital literacy, critical thinking, collaboration, communication, and creativity, within MIPA education. A comprehensive analysis of peer-reviewed studies published between 2018 and 2025 was conducted to identify key pedagogical approaches that effectively enhance these skills. Methods such as Project-Based Learning (PBL), Inquiry-Based Learning (IBL), and Technology-Enhanced Learning (TEL) were identified as prominent strategies for promoting student engagement and developing transversal skills alongside domain-specific knowledge. Despite the promising outcomes, the review also highlights challenges related to curriculum integration, teacher preparedness, and resource allocation. It is concluded that a holistic approach, involving curriculum reforms, continuous professional development for educators, and cross-disciplinary collaboration, is essential to successfully embed 21st-century skills within MIPA education. This review provides valuable insights into the role of contemporary learning methods in shaping future-ready students equipped with the competencies needed to navigate an increasingly complex and technology-driven world.